2014
DOI: 10.1007/s00270-013-0824-7
|View full text |Cite
|
Sign up to set email alerts
|

CT-Assisted Sympathicolysis as an Additional Minimally Invasive Therapeutic Option in Primary Focal Plantar Hyperhidrosis

Abstract: After conservative measures have been exhausted or as a complement to the existing therapy regimen, CT-assisted sympathicolysis represents a therapeutic option low in side effects that provides a marked benefit to patients with primary, focal hyperhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…6,16,18 There was a variation from 7.5 to 90% CS after mechanical sympathectomy and from 1.5 to 34% after chemical sympathicolysis; since there is no standardization in the questioning of this complication, it is suggested the possibility of underreporting of its presence. All studies performed lumbar sympathectomy after TS, a surgical procedure with 16 Satisfaction rate 37 months Reisfeld et al 17 -24 months Rieger et al 18 Satisfaction rate 24 months Kim et al 19 Satisfaction rate 14.3 months average Loureiro et al 20 QoL 15 Chemical sympathicolysis L3/L4 35 6 1 Rieger et al 16 Mechanical sympathectomy L2/L3/L4 96 --Reisfeld et al 17 Mechanical sympathectomy L3/L4 * L2 63 11 0 Rieger et al 18 Mechanical sympathectomy L3/L4 90 38 3 Kim et al 19 Chemical sympathicolysis L3 to L5 69 3 1 Loureiro et al 20 Mechanical (2015) Yun (2017) 441 405 τ 2 = 0.00; χ 2 = 3.24, df = 6 (P = 0.78); I 2 = 0% Z = 3.07 (P = 0.002) Heterogeneity:…”
Section: Discussionmentioning
confidence: 99%
“…6,16,18 There was a variation from 7.5 to 90% CS after mechanical sympathectomy and from 1.5 to 34% after chemical sympathicolysis; since there is no standardization in the questioning of this complication, it is suggested the possibility of underreporting of its presence. All studies performed lumbar sympathectomy after TS, a surgical procedure with 16 Satisfaction rate 37 months Reisfeld et al 17 -24 months Rieger et al 18 Satisfaction rate 24 months Kim et al 19 Satisfaction rate 14.3 months average Loureiro et al 20 QoL 15 Chemical sympathicolysis L3/L4 35 6 1 Rieger et al 16 Mechanical sympathectomy L2/L3/L4 96 --Reisfeld et al 17 Mechanical sympathectomy L3/L4 * L2 63 11 0 Rieger et al 18 Mechanical sympathectomy L3/L4 90 38 3 Kim et al 19 Chemical sympathicolysis L3 to L5 69 3 1 Loureiro et al 20 Mechanical (2015) Yun (2017) 441 405 τ 2 = 0.00; χ 2 = 3.24, df = 6 (P = 0.78); I 2 = 0% Z = 3.07 (P = 0.002) Heterogeneity:…”
Section: Discussionmentioning
confidence: 99%
“…The needle was then withdrawn, and the patient was maintained in the supine position for 4 hours, while the pulse, blood pressure, and respiration were monitored. [6][7][8][9][10]15 Evaluation of the Severity of Palmar Hyperhidrosis…”
Section: Botulinum Toxin Type a Injectionmentioning
confidence: 99%
“…Thoracic sympathectomy is considered the best treatment, and is adopted by the majority of thoracic surgical centers worldwide because of its safety and ability to achieve a definitive cure. [6][7][8][9][10] However, BTX-A injection is a promising new therapeutic option for palmar hyperhidrosis that is administered on an outpatient basis, and has minimal adverse reactions, low invasiveness, and high efficacy. [11][12][13] The present retrospective, observational study was a comparative analysis of patients with palmar hyperhidrosis who underwent either thoracic sympathectomy or BTX-A injection.…”
Section: Introductionmentioning
confidence: 99%
“…The DLQI was identified in studies conducted globally, including in the UK (n = 9 103,232,261,262,267,268,275 ), the USA and Canada (n = 8 77,107,139,173,176,208,222,263 ), Italy (n = 7 101,102,106,214,223,266,272 ), Germany (n = 5 69,158,227,270,271 ), Sweden (n = 4 114,116,117,128 ), Greece (n = 3 [119][120][121] ), Ireland (n = 2 265,274 ), Iran (n = 2 170,264 ), Spain (n = 2 210,230 ), Australia (n = 1 ) or surgical reviews or reviews of surgery compared with dermatology (n = 3 147,267,273 ). The DLQI was used in studies to measure quality of life on various areas of the body; studies of axillary sweating combined with other parts of the body, such as palms or feet, were most common (n = 26 54,56,69,77,101,103,106,107,…”
Section: Review Of Quality-of-life Measures/toolsmentioning
confidence: 99%
“…The DLQI was used in studies to measure quality of life on various areas of the body; studies of axillary sweating combined with other parts of the body, such as palms or feet, were most common (n = 26 54,56,69,77,101,103,106,107,114,[119][120][121]139,147,158,170,173,176,214,221,223,263,266,273,274 ). Studies were identified of the palm or palm and foot combined (n = 11 61,128,208,222,230,264,265,[269][270][271][272] ) and of other combinations including the face, palm and/or foot or generalised hyperhidrosis (n = 11 116,117,210,217,227,232,261,262,267,268,275 ).…”
Section: Review Of Quality-of-life Measures/toolsmentioning
confidence: 99%